Preparation method and application of transparent super-hydrophobic coating
By forming a superhydrophobic coating with PVDF-TrFE/PDMS nanofiber structure on optical glass, the problems of transparency loss and poor adhesion in the prior art are solved, and the combination of high transparency and good hydrophobic properties is achieved, which is suitable for waterproofing and Anti-ice application.
Patent Information
- Application Number
- CN202411309330.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The existing superhydrophobic coatings have problems of loss of transparency and poor adhesion in the application of optical glass, resulting in poor light scattering and freezing delay effects.
Polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE) and siloxane (PDMS) are blended with solvents, and crosslinking agent layer and accelerator layer are formed on the substrate surface through electrospinning technology to form a tight adhesion. nanofiber structure improves transparency and hydrophobicity.
A transparent superhydrophobic coating with a light transmittance of more than 85% in the range of 400 to 1200 nm is achieved, and it has good scratch resistance and water impact resistance, maintaining superhydrophobicity and high transparency.
Smart Images

Figure CN119243343A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of hydrophobic coatings, and in particular relates to a preparation method and application of a transparent super-hydrophobic coating. Background Art
[0002] Due to changes in ambient temperature and humidity, the accumulation of water droplets, fog and frost can significantly reduce the transparency of optical glass, which affects its application in areas such as automotive windshields, architectural windows and camera lenses. To address this problem, researchers have developed various functional coatings designed to repel or attract water, including superhydrophobic and superhydrophilic coatings. These coatings have been shown to effectively mitigate the negative effects of moisture accumulation.
[0003] However, compared with superhydrophilic coatings, superhydrophobic coatings inspired by lotus leaves enable water droplets to roll off, achieving self-cleaning function; in addition, there are air pockets in the micro / nanostructure of superhydrophobic coatings, which can delay the freezing process by hindering heat transfer and reducing the contact area between the liquid and the surface, thereby preventing the accumulation of fog and frost. Superhydrophobic surfaces have been developed to integrate anti-icing, anti-frost and self-healing functions. However, achieving a balance between surface roughness, transparency and durability remains challenging.
[0004] Methods for constructing super-hydrophobic coatings include chemical vapor deposition, etching, template-based, self-assembly, and sol-gel processes, and the resulting super-hydrophobic coatings usually exhibit uneven and uncontrollable surface morphology, which results in light scattering on the surface of the super-hydrophobic coating, thus adversely affecting the transparency of optical glass.
[0005] In contrast, electrospinning technology can produce continuous fibers with adjustable diameter, thickness, porosity and roughness, which has the advantage of regulating superhydrophobicity and transparency at the micro-nano scale. However, the superhydrophobic coating prepared by electrospinning technology has the following defects: 1. Transparency loss caused by reflection / refraction at the air-fiber interface; 2. Poor adhesion between the glass substrate and the coating. In order to avoid transparency loss caused by reflection / refraction at the air-fiber interface, the composition and pore morphology of the nanofiber membrane must be precisely controlled. Summary of the invention
[0006] In order to improve the deficiencies of the prior art, the present invention provides a method for preparing a transparent super-hydrophobic coating and its application, which can improve at least one of the following problems: reducing transparency loss and improving the adhesion between the coating and the substrate.
[0007] As mentioned above, in a first aspect, the present invention provides a method for preparing a transparent super-hydrophobic coating, comprising the following steps:
[0008] Polyvinylidene fluoride-trifluoroethylene copolymer, PDMS and a solvent are mixed to obtain a spinning solution, and a super-hydrophobic transparent coating is formed on the surface of a substrate by electrospinning.
[0009] According to an embodiment of the present invention, the mass ratio of the polyvinylidene fluoride-trifluoroethylene copolymer to PDMS is 1:0-1:10, preferably the mass ratio of the polyvinylidene fluoride-trifluoroethylene copolymer to PDMS is 1:0-1:6, for example, 1:0, 1:1, 1:2, 1:3, 1:4.
[0010] According to an embodiment of the present invention, in the spinning solution, the concentration of the polyvinylidene fluoride-trifluoroethylene copolymer and PDMS is 5-30wt%, preferably the concentration of the polyvinylidene fluoride-trifluoroethylene copolymer and PDMS is 10-20wt%, for example 15wt%.
[0011] According to an embodiment of the present invention, the solvent is selected from one or more of methanol, ethanol, acetone, DMF, THF, and n-hexane, for example, DMF or a mixed solution of DMF and THF.
[0012] According to an embodiment of the present invention, blending polyvinylidene fluoride-trifluoroethylene copolymer, PDMS and a solvent to obtain a spinning solution comprises the following steps: adding polyvinylidene fluoride-trifluoroethylene copolymer and PDMS to a DMF solution, mixing until dissolved, and obtaining a spinning solution.
[0013] According to an embodiment of the present invention, the mass ratio of the polyvinylidene fluoride-trifluoroethylene copolymer to PDMS and the solvent is 1:(1-6), preferably the mass ratio of the polyvinylidene fluoride-trifluoroethylene copolymer to PDMS and the solvent is 1:(1-4), for example 1:1.
[0014] According to an embodiment of the present invention, the mixing is performed at a temperature of room temperature to 80°C, preferably at a temperature of 50 to 70°C, for example, 60°C.
[0015] According to an embodiment of the present invention, the mixing time is 1 to 8 hours, preferably the mixing time is 2 to 6 hours, for example, 3 hours.
[0016] According to an embodiment of the present invention, the mixing is performed under stirring conditions.
[0017] According to an embodiment of the present invention, blending polyvinylidene fluoride-trifluoroethylene copolymer and PDMS to obtain a spinning solution specifically includes the following steps: firstly mixing PDMS with a curing agent to obtain a PDMS prepolymer, and then adding the PDMS prepolymer and polyvinylidene fluoride-trifluoroethylene copolymer to a mixed solution of DMF and THF, and mixing until dissolved.
[0018] According to an embodiment of the present invention, before forming a super-hydrophobic transparent coating on the surface of a substrate by electrospinning, the following step is also included: cleaning the surface of the substrate.
[0019] According to an embodiment of the present invention, cleaning the surface of the substrate comprises the following steps: ultrasonically cleaning the substrate with isopropyl alcohol, acetone and deionized water and drying.
[0020] According to an embodiment of the present invention, the drying is performed at a temperature of 30-100°C, for example, 60°C.
[0021] According to an embodiment of the present invention, the drying time is 10 to 60 minutes, for example, 30 minutes.
[0022] According to an embodiment of the present invention, after cleaning the surface of the substrate and before forming a super hydrophobic transparent coating on the surface of the substrate by electrospinning, the following steps are also included: coating a cross-linking agent on the surface of the substrate to form a cross-linking agent layer, wherein the cross-linking agent layer is used to cross-link with polyvinylidene fluoride-trifluoroethylene copolymer and PDMS to form a transparent super hydrophobic coating.
[0023] According to an embodiment of the present invention, the crosslinking agent is selected from one or more of trimethylchlorosilane, triethoxysilane, methyltriethoxysilane, trimethoxysilane, and methyltrimethoxysilane, for example, trimethylchlorosilane.
[0024] According to an embodiment of the present invention, coating the crosslinking agent on the substrate surface comprises the following steps: dissolving the crosslinking agent in a solvent to form a crosslinking agent solution, and coating the crosslinking agent solution on the substrate surface.
[0025] According to an embodiment of the present invention, the concentration of the cross-linking agent solution is 0.1-0.5 wt %, for example, 0.2 wt %.
[0026] As an example, the cross-linking agent solution is a trimethylchlorosilane n-hexane solution with a concentration of 0.2 wt %.
[0027] According to an embodiment of the present invention, the substrate is selected from glass, metal, cloth, filter paper, etc., for example, glass.
[0028] According to an embodiment of the present invention, after forming a crosslinker layer on the substrate surface and before forming a super-hydrophobic transparent coating on the substrate surface by electrospinning, the following step is also included: coating a promoter on the surface of the crosslinker layer to form a promoter layer.
[0029] According to an embodiment of the present invention, coating an accelerator on the surface of the crosslinker layer comprises the following steps: mixing a PDMS prepolymer with a curing agent, coating the mixture on the surface of the crosslinker layer, and curing the mixture under ultraviolet light to form an accelerator layer.
[0030] According to an embodiment of the present invention, the mass ratio of the PDMS prepolymer to the curing agent is (5-20):1, preferably the mass ratio of the PDMS prepolymer to the curing agent is (10-15):1, for example, 10:1.
[0031] According to an embodiment of the present invention, the curing agent is selected from at least one of a platinum-catalyzed addition curing agent, hydrogen-containing silicone oil, methoxysilane, ethoxysilane, dipropylbenzene peroxide, benzyl peroxide, tert-butyl peroxide, etc., for example, a platinum-catalyzed addition curing agent.
[0032] According to an embodiment of the present invention, the electrospinning is performed under a condition of 11-20 kV at a constant flow rate of 0.1-3 mL / h, for example, under a constant flow rate of 0.5 mL / h at 14.5 kV.
[0033] According to an embodiment of the present invention, after the electrospinning, the process further comprises the following step: drying the electrospinned substrate.
[0034] According to an embodiment of the present invention, the drying is performed at a temperature of 30-100°C, for example, 60°C.
[0035] According to an embodiment of the present invention, the drying time is 2 to 6 hours, for example, 4 hours.
[0036] According to an embodiment of the present invention, the initial contact angle of the transparent superhydrophobic coating is 154.6°, and the rolling angle is about 9°.
[0037] According to an embodiment of the present invention, the sliding angle of the transparent super hydrophobic coating after continuous water spraying for 45 minutes is about 20°.
[0038] According to an embodiment of the present invention, the transmittance of the transparent super hydrophobic coating to light in the range of 400 to 1200 nm is greater than 80%, preferably, the transmittance of the transparent super hydrophobic coating to light in the range of 400 to 1200 nm is greater than 85%, and further preferably, the transmittance of the transparent super hydrophobic coating to light in the range of 400 to 1200 nm is ≥90%.
[0039] In a second aspect, the present invention provides an application of a transparent super-hydrophobic coating prepared by the method described above in glass waterproofing.
[0040] Beneficial Effects
[0041] 1) The present invention increases the transmittance by introducing a highly light-transmitting material PDMS onto a substrate, thereby obtaining a light-transmitting coating with a light transmittance of more than 85% in the range of 400 to 1200 nm; at the same time, the light-transmitting coating has not only good scratch resistance, but also good hydrophobicity: the initial contact angle is 154.6°, the rolling angle is about 9°, and the hydrophobicity is still maintained after continuous water spraying for 45 minutes, the water contact angle (WCA) decreases slightly, and the sliding angle (SA) increases slightly to about 20°.
[0042] 2) The present invention forms a promoter layer and a cross-linking agent layer on the substrate in advance, and the cross-linking agent layer can increase the connection strength between the promoter layer and the substrate, so that the cross-linking agent layer and the substrate are not only connected by hydrogen bonds, but also form chemical bonds through the cross-linking agent layer; and the cross-linking agent layer is used to cross-link with the polyvinylidene fluoride-trifluoroethylene copolymer and PDMS in the electrospinning solution, so that the fibers formed by electrospinning are closely adhered to the substrate, and the super-hydrophobic coating formed by electrospinning presents a mutually cross-linked nanofiber structure, and the fibers are cross-linked to form a network structure, and there are a large number of pores in the network structure, thereby forming a super-hydrophobic coating with both super-hydrophobicity and optical transparency. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The schematic diagram and flow chart of the method for preparing a transparent super-hydrophobic coating according to the present invention;
[0044] Figure 2 The scanning electron microscope image and fiber size distribution diagram of the electrospinning coating prepared in Example 1 of the present invention;
[0045] Figure 3 This is a comparison chart of the transmittance of the electrospinning coating prepared under different conditions in Example 1 of the present invention;
[0046] Figure 4 This is a pencil abrasion resistance test of the electrospinning coating prepared under the condition of G being 1:3 in Example 1 of the present invention;
[0047] Figure 5 This is a water flow impact resistance test of the super-hydrophobic electrospinning coating prepared under the condition of G being 1:3 in Example 1 of the present invention;
[0048] Figure 6 The actual image and scanning electron microscope image of the super-hydrophobic electrospinning coating prepared under the condition of G being 1:1 in Example 2 of the present invention;
[0049] Figure 7 The actual image and scanning electron microscope image of the super-hydrophobic electrospinning coating prepared under the condition of G being 1:4 in Example 2 of the present invention. DETAILED DESCRIPTION
[0050] The super-hydrophobic coating of the present invention and its preparation method and application will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary and explain the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies realized based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0051] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0052] Example 1
[0053] A method for preparing a transparent super-hydrophobic coating comprises the following steps:
[0054] First, the glass sheet was ultrasonically cleaned with isopropanol, acetone and deionized water, and then dried in an oven at 60°C for 30 minutes. A 0.2wt% MTS (methyltrichlorosilane) solution (with n-hexane as solvent) was prepared by magnetic stirring, applied to the surface of the glass sheet with a brush, and dried at 60°C for 15 minutes to obtain a crosslinker layer; a PDMS (polydimethylsiloxane) prepolymer and a curing agent (platinum catalyzed addition curing agent, from Sylgard 184B) were mixed in a weight ratio of 10:1, and stirred at 1000 rpm for 15 minutes at room temperature to make it uniform, forming a promoter solution, coating the promoter solution on the crosslinker layer, and curing under ultraviolet light to achieve a strong bond, forming a promoter layer film, and obtaining a pretreated glass sheet.
[0055] In order to electrospin PVDF-TrFE (polyvinylidene fluoride-trifluoroethylene) / PDMS copolymer mixture (the mass ratio of PVDF-TrFE to PDMS ranges from 1:0 to 1:4, i.e., G-1:0 / 1:1 / 1:2 / 1:3 / 1:4) nanofibers, the PVDF-TrFE / PDMS copolymer mixture was mixed and dissolved with DMF solution at a mass ratio of 1:1 to form an electrospinning solution with a concentration of 15wt%, stirred at 60°C for 3 hours, and electrospun onto a pretreated glass sheet at a constant flow rate of 0.5mL / h at 14.5kV. The electrospinning process parameters were optimized by adjusting the time to achieve the desired thickness and water contact angle, and then the coated glass sheet was dried at 60°C for 4 hours to remove the residual solvent.
[0056] See also Figure 1As shown, it is the principle diagram and process flow chart of electrospinning of this embodiment. In order to improve the firmness of transparent super-hydrophobic electrospun (TESH) nanofibers, the present invention first performs a pretreatment step of MTS silanization (TMS-s) on glass, then deposits PDMS prepolymer to form a promotion layer, and then coats PVDF-TrFE / PDMS nanofibers on the promotion layer by electrospinning to form a transparent super-hydrophobic coating, thereby obtaining a glass sheet with a super-hydrophobic coating.
[0057] See also Figure 2 , which is a scanning electron microscope image of the electrospinning coating prepared in this embodiment, it can be seen from the image that the coating is a cross-linked nanofiber structure, and the fibers are cross-linked to form a network structure, and the average diameter of the fibers is 101.78±3nm.
[0058] See also Figure 3 As shown in the figure, the transmittance comparison chart of the electrospinning coating prepared under different conditions in this embodiment shows that when the mass ratio of PVDF-TrFE to PDMS is 1:3, the transmittance effect is optimal, and the transmittance is ≥90% under the irradiation of light with a wavelength in the range of 400nm to 1200nm; and when the mass ratio of PVDF-TrFE to PDMS is in the range of 1:1 to 1:4, the transmittance is ≥80% under the irradiation of light with a wavelength in the range of 400nm to 1200nm, that is, the electrospinning coating prepared by the present invention has good transmittance.
[0059] See also Figure 4 As shown in the figure, the super-hydrophobic coating prepared by G-1:3 in this embodiment is subjected to a wear resistance test according to the ASTM D3363 standard. The mechanical robustness of the super-hydrophobic coating is verified by a pencil hardness test, showing that it has scratch resistance when the pencil hardness reaches 4H; however, when a pencil with a hardness exceeding 6H is used, scratches appear on the surface. The test shows that the super-hydrophobic coating prepared by G-1:3 has a significant hardness of 4H and has good scratch resistance according to the ASTM D3363 standard.
[0060] See also Figure 5 As shown in the figure, the water flow impact resistance test of the super-hydrophobic coating prepared under the condition of G being 1:3 in this embodiment, the test results show that the initial contact angle of the super-hydrophobic coating is 154.6°, the rolling angle is about 9°, and the hydrophobicity is still maintained after 45 minutes of continuous water spraying, the water contact angle (WCA) decreases slightly, and the sliding angle (SA) increases slightly to about 20°, indicating that it has good hydrophobicity.
[0061] Example 2
[0062] A method for preparing a transparent super-hydrophobic coating comprises the following steps:
[0063] First, the glass sheet was ultrasonically cleaned with isopropanol, acetone and deionized water, and then dried in an oven at 60°C for 30 minutes. A 0.5wt% MTS (methyltrichlorosilane) solution (with n-hexane as solvent) was prepared by magnetic stirring, applied to the surface of the glass sheet with a brush, and dried at 60°C for 15 minutes to obtain a crosslinker layer; a PDMS (polydimethylsiloxane) prepolymer and a curing agent (platinum catalyzed addition curing agent) were mixed in a weight ratio of 20:1, and stirred at 1000 rpm for 15 minutes at room temperature to make it uniform, forming a promoter solution, coating the promoter solution on the crosslinker layer, and curing under ultraviolet light to achieve a firm bond, forming a promoter layer film, and obtaining a pretreated glass sheet.
[0064] In order to carry out electrospinning of PVDF-TrFE (polyvinylidene fluoride - trifluoroethylene) / PDMS copolymer mixture (the mass ratio of PVDF-TrFE to PDMS is from 1:0 to 1:4, i.e. G-1:0 / 1:1 / 1:2 / 1:3 / 1:4) nanofibers, the PVDF-TrFE / PDMS copolymer mixture is mixed and dissolved with DMF:THF (1:1) mixed solvent at a mass ratio of 1:1 to form an electrospinning solution with a concentration of 10wt%, stirred at room temperature for 8 hours, and electrospun onto a pretreated glass sheet at a constant flow rate of 3mL / h at 11kV. The electrospinning process parameters are optimized by adjusting the time to achieve the desired thickness and water contact angle, and then the coated glass sheet is dried at 60°C for 4 hours to remove the residual solvent to obtain a glass sheet with a super hydrophobic coating.
[0065] See also Figure 6 As shown, the super hydrophobic coating prepared in this embodiment has a cross-linked nanofiber structure, and the fibers are cross-linked to form a network structure, and has good light transmittance. After testing, the transmittance is greater than 81.5%.
[0066] Example 3
[0067] A method for preparing a transparent super-hydrophobic coating comprises the following steps:
[0068] First, the glass sheet was ultrasonically cleaned with isopropanol, acetone and deionized water, and then dried in an oven at 60°C for 30 minutes. A 0.1wt% MTS (methyltrichlorosilane) solution (with n-hexane as solvent) was prepared by magnetic stirring, applied to the surface of the glass sheet with a brush, and dried at 60°C for 60 minutes to obtain a crosslinker layer; a PDMS (polydimethylsiloxane) prepolymer and a curing agent (platinum catalyzed addition curing agent) were mixed in a weight ratio of 10:1, and stirred at 1000 rpm for 30 minutes at room temperature to make it uniform, forming a promoter solution, coating the promoter solution on the crosslinker layer, and curing under ultraviolet light to achieve a firm bond, forming a promoter layer film, and obtaining a pretreated glass sheet.
[0069] In order to carry out electrospinning of PVDF-TrFE (polyvinylidene fluoride-trifluoroethylene) / PDMS copolymer mixture (the mass ratio of PVDF-TrFE to PDMS is from 1:0 to 1:4, i.e. G-1:0 / 1:1 / 1:2 / 1:3 / 1:4) nanofibers, the PVDF-TrFE / PDMS copolymer mixture is mixed and dissolved with DMF:THF (1:1) mixed solvent at a mass ratio of 1:1 to form an electrospinning solution with a concentration of 20wt%, stirred at 60°C for 3 hours, and electrospun onto a pretreated glass sheet at a constant flow rate of 0.1mL / h at 20kV. The electrospinning process parameters are optimized by adjusting the time to achieve the desired thickness and water contact angle, and then the coated glass sheet is dried at 60°C for 4 hours to remove the residual solvent to obtain a glass sheet with a super hydrophobic coating.
[0070] See also Figure 7 As shown, the super hydrophobic coating prepared in this embodiment has a cross-linked nanofiber structure, and the fibers are cross-linked to form a network structure, which has good hydrophobicity and good light transmittance. After testing, the transmittance is greater than 80%.
[0071] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a transparent super-hydrophobic coating, characterized in that: The preparation method comprises the following steps: A polyvinylidene fluoride-trifluoroethylene copolymer, PDMS and a solvent are mixed to obtain a spinning solution, and a super-hydrophobic transparent coating is formed on the surface of a substrate by electrospinning; the mass ratio of the polyvinylidene fluoride-trifluoroethylene copolymer to the PDMS is 1:0 to 1:10, and the concentrations of the polyvinylidene fluoride-trifluoroethylene copolymer and the PDMS in the spinning solution are 5 to 30 wt%.
2. The method for preparing a transparent super-hydrophobic coating according to claim 1, wherein: The solvent is selected from one or more of methanol, ethanol, acetone, DMF, THF and n-hexane.
3. The method for preparing a transparent super-hydrophobic coating according to claim 1, characterized in that: The method of mixing polyvinylidene fluoride-trifluoroethylene copolymer, PDMS and a solvent to obtain a spinning solution comprises the following steps: adding polyvinylidene fluoride-trifluoroethylene copolymer and PDMS into a DMF solution, mixing until dissolved, and obtaining a spinning solution. Preferably, the mass ratio of the polyvinylidene fluoride-trifluoroethylene copolymer to PDMS and the solvent is 1:(1-6). Preferably, the mixing is performed at a temperature of room temperature to 80° C., and the mixing time is 1 to 8 hours.
4. The method for preparing a transparent super-hydrophobic coating according to any one of claims 1 to 3, characterized in that: Before forming a super-hydrophobic transparent coating on the substrate surface by electrospinning, the following step is also included: cleaning the substrate surface.
5. The method for preparing a transparent super-hydrophobic coating according to claim 4, characterized in that: After cleaning the substrate surface, before forming a super-hydrophobic transparent coating on the substrate surface by electrospinning, the following steps are also included: coating a cross-linking agent on the substrate surface to form a cross-linking agent layer, wherein the cross-linking agent layer is used to cross-link with polyvinylidene fluoride-trifluoroethylene copolymer and PDMS to form a transparent super-hydrophobic coating. Preferably, the crosslinking agent is selected from one or more of trimethylchlorosilane, triethoxysilane, methyltriethoxysilane, trimethoxysilane and methyltrimethoxysilane.
6. The method for preparing a transparent super-hydrophobic coating according to claim 4, characterized in that: Coating the crosslinking agent on the surface of the substrate comprises the following steps: dissolving the crosslinking agent in a solvent to form a crosslinking agent solution, and coating the crosslinking agent solution on the surface of the substrate. Preferably, the concentration of the cross-linking agent solution is 0.1-0.5 wt %.
7. The method for preparing a transparent super-hydrophobic coating according to claim 5, characterized in that: After the crosslinking agent layer is formed on the substrate surface and before the super-hydrophobic transparent coating is formed on the substrate surface by electrospinning, the method further includes the following steps: coating a promoter on the surface of the crosslinking agent layer to form a promoter layer. Preferably, coating the accelerator on the surface of the crosslinking agent layer comprises the following steps: mixing the PDMS prepolymer with the curing agent, coating the mixture on the surface of the crosslinking agent layer, and curing the mixture under ultraviolet light to form the accelerator layer. Preferably, the mass ratio of the PDMS prepolymer to the curing agent is (5-20):
1. Preferably, the curing agent is selected from at least one of a platinum-catalyzed addition curing agent, hydrogen-containing silicone oil, methoxysilane, ethoxysilane, dipropylbenzene peroxide, benzyl peroxide, tert-butyl peroxide, etc., for example, a platinum-catalyzed addition curing agent.
8. The method for preparing a transparent super-hydrophobic coating according to any one of claims 1 to 3, characterized in that: The electrospinning is performed under the conditions of 11 to 20 kV and a constant flow rate of 0.1 to 3 mL / h.
9. The method for preparing a transparent super-hydrophobic coating according to any one of claims 1 to 3, characterized in that: After the electrostatic spinning, the method further comprises the following step: drying the electrostatically spun substrate.
10. Use of a transparent super-hydrophobic coating prepared by the method according to any one of claims 1 to 9 in glass waterproofing.
Citation Information
Patent Citations
Method for preparing PDMS / PVDF composite membrane
CN101545213A
Material with super-hydrophobic micro-nano particle surface and preparation method of material
CN113770005A
Method for constructing super-hydrophobic PVDF nanofiber membrane based on interface self-polymerization and application of super-hydrophobic PVDF nanofiber membrane
CN113842791A
Preparation of silicon rubber-polyvinylidene fluoride electrospun nanofiber hydrophobic microporous composite membrane
CN113877445A
KR20200009428A
Cited By
High-orientation super-hydrophobic bionic anti-icing anticorrosive coating and preparation method thereof
CN121652645A
